Somatostatin analogue-induced pancreatic exocrine insufficiency in patients with neuroendocrine tumors: results of a prospective observational study. (3rd July 2018) - Lamarca, Angela; McCallum, Lynne; Nuttall, Christina; Barriuso, Jorge; Backen, Alison; Frizziero, Melissa; Leon, Rebecca; Mansoor, Was; McNamara, Mairéad G; Hubner, Richard A.; Valle, Juan W
ABSTRACT: Background: Patients with advanced well-differentiated neuroendocrine tumours (Wd-NETs) are commonly treated with somatostatin analogues (SSAs). Some patients may develop SSA-related side effects such as pancreatic exocrine insufficiency (PEI). Methods: In this prospective, observational study, the frequency of SSA-induced PEI in 50 sequential patients with advanced Wd-NETs treated with SSAs was investigated. Toxicity was assessed monthly and faecal elastase-1 (FE1) and quality of life (QoL) were assessed 3-monthly. Results: The median age was 65.8 years, 58% were male and the majority (92%) of patients had metastatic disease; patients received 4-weekly long acting octreotide (60%) or lanreotide (40%). Twelve patients (24%) developed SSA-related PEI after a median of 2.9 months from SSA initiation; FE1 was a reliable screening tool for PEI, especially in symptomatic (abdominal bloating, flatulence and/or diarrhea) patients (risk ratio 8.25 (95% confidence interval 1.15–59.01)). Most of these patients (11/12; 92%) required PERT. Other SSA-related adverse events (any grade) included flatulence (50%), abdominal pain (32%), diarrhoea (30%) and fatigue (20%). Development of PEI did not significantly worsen overall QoL, however gastrointestinal symptoms and diarrhoea were increased. Conclusion: This study demonstrated that PEI occurs at a higher rate than previously reported; clinicians need to diagnose and treat this SSA-related adverse-event which occurs in 1 in 4 patients with Wd-NETs treated with SSAs. Screening with FE1 in symtomatic patients is recommend.